Hubungan antara Koordinasi Mata Kaki dan Persepsi Kinestetik dengan Keterampilan Servis Permainan Sepak Takraw pada Sekolah Kebakatan Olahraga - Basman Basman; Edy Gunawan (STKIP PGRI SITUBONDO, 2022)
This study aims to determine the relationship between eye-foot coordination and service skills in sepak takraw, the relationship between kinesthetic perception and service skills in sepak takraw and the relationship between eye-foot coordination and kinesthetic perception simultaneously with service skills in sepak takraw. The study used a correlational method with a research population of 114 people and a research sample of 30 people, using a purposive sampling technique with the help of an instrument to measure eye-foot coordination (Wall pass sho test), kinesthetic perception (perception distance jump test), and a test to serve as many as 5 times. The results of the analysis show that there is a relationship between eye-foot coordination and service skills, which is a simple linear regression equation = 33.123 + 0.956 X1 with a coefficient of determination (r2) =48%, a relationship between kinesthetic perception and takraw service skills=-8.472 +0.802 X2 with a coefficient of determination. (r2) =47%, and the simultaneous relationship between eye-foot coordination =-874 + 0.676 X1 + 0.557X2 with a coefficient of determination (r2) =67%. The study concluded that there was a significant relationship between eye-foot coordination and kinesthetic perception of the service skills of the sepak takraw game in sports talent schools.